Program Magang di Sekretariat Dprd Sumatera Utara dan Dinamika Partisipasi Politik Mahasiswa dalam Demokrasi Daerah - Mardian Idris Harahap; Ayu Wantika; Nayla Putri Kamila; Fitriani Fitriani; Reyza Dian Isnaini Prasetya; Muhammad Albani (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
An internship program is a form of experiential learning designed to bridge academic theory with professional practice, particularly in the fields of government administration and public policy. This study was motivated by the importance of students’ understanding of the operational mechanisms of regional legislative bodies and the dynamics of public political participation within the North Sumatra Provincial Regional Representative Council (DPRD). This study employs a descriptive qualitative method using direct observation during internship activities, documentation, and analysis of institutional activities at the Secretariat of the North Sumatra DPRD. The objective of this study is to understand the role of the DPRD Secretariat in supporting legislative, budgetary, and oversight functions, while also analyzing the dynamics of student political participation as reflected through demonstrations within the DPRD environment. The results of the study indicate that the internship program provides practical experience for students in understanding government administrative processes and the mechanisms of regional legislative work. In addition, this study also found that the student demonstrations that took place at the North Sumatra Regional Representative Council (DPRD) constitute a form of political participation and social control over public policy, reflecting the role of students as agents of change in democracy. To reduce the potential for conflict between students, security forces, and government institutions, it is necessary to strengthen political communication and institutional dialogue mechanisms, as well as to improve policy literacy among students so that political participation can take place more constructively within the democratic system.